Community science for the wise use of Colombo’s wetlands - Jirasinha, Radheeka (International Water Management Institute, 2023)
In Colombo, Sri Lanka, urban wetlands provide flood protection, water purification, and livelihoods for many local communities. But wetland loss and degradation continue to threaten these precious ecosystems. https://www.iwmi.org/wetlandsday2023